Effects of Surgical Intervention and Continuous Positive Airway Pressure Therapy on Velopharyngeal Structure and Function: A Case Report. (April 2019) - Schenck, Graham C.; Perry, Jamie L.; Kollara, Lakshmi; Kuehn, David P.
Changes to the velum and velopharyngeal muscles following Furlow double-opposing Z-plasty in a 7-year-old female with submucous cleft palate and velopharyngeal dysfunction (VPD) were evaluated. Perceptual, instrumental (ie, nasometry and aerodynamic pressure flow), and research magnetic resonance imaging analyses were used during pre- and postsurgical time points at a university research clinic. Continuous positive airway pressure (CPAP) therapy was trialed following a failed surgery for residual VPD in the patient. Increases in velar length and thickness and decreases in levator veli palatini muscle angle of origin and contraction were observed following the Furlow double-opposing Z-plasty surgery. Variable improvements in residual hypernasality following the home-based CPAP therapy protocol were observed.